Uji Coba Penanaman Lima Jenis Dipterokarpa pada Lahan Bekas Tambang di Pt. Kitadin, Kalimantan Timur - Adi Susilo (Universitas Sebelas Maret, 2016)
Increased use of forest land for mining activities in East Kalimantan generate huge degradation land. Land rehabilitation need to be conducted to lessen the mining impact. This study was conducted to test the suitability of five dipterocarp species planted on ex-coal mining land. The studied species were Shorea agamii, Shorea atrinervosa, Shorea Belangeran, Cotylelobium burckii, and Parashorea smythiesii that was planted under stands of four years old five pioneer species i.e., (Trembesi, Waru, Sengon Buto, Gmelina, and Johar). Of the 1,250 planted trees only 128 (10.24%) were still alive in the second year. In the shade of a tamarind stands, Gmelina, Waru, Sengon and Johar consecutive leaving only 61 trees (24%), 23 trees (9.2%), 20 trees (8%), 19 trees (7.6%) and five trees (2 %). The best two diptrocarps species were Parashorea smythiesii and Shorea balangeran and the best shading trees was trembesi